PENGARUH KEPEMIMPINAN OLAH DAN KOMITMEN ORGANISASI TERHADAP KINERJA GURU SMP NEGERI TELUK KERAMAT - Herman, .; Radiana, Usman; Chiar, H.M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractÂ This research is commonly purposed to reveal how is headmaster leadership influence toward teacher action, is the commitment organization influence to teacher action, is the headmaster leadership significant to the teacher of SMP Negeri Sub-district Teluk Keramat. This research used quantitative approach, with causal study type (effect study). The populations in this research were 186 teachers. While the sample consist of 127 teachers. The instrument of this research was questionnaires with likert scale, technique of analysis which is used multiple linear regression. Data analysis is done by using spss program. Version 20 for window.From research finding is found that: (1) headmaster leadership influence (X1) is effected significant to teacher action (Y) Beta (b1) was about 0,243 = 24,3 %. 2) commitment organization influence (X2) to teacher action (Y) Beta (b1) was about 0,323 = 32.3 %. 3) headmaster leadership influence (X1) and commitment organization (X2) toward teacher action was 0, 281 or 28,1 %. Â Keywords: Leadership, Commitment, Teacher Action Â